Oxygen control: the often overlooked but essential piece to create better in vitro systems. Issue 6 (27th January 2022) - Palacio-Castañeda, Valentina; Velthuijs, Niels; Le Gac, Séverine; Verdurmen, Wouter P. R.
Abstract : Variations in oxygen levels play key roles in numerous physiological and pathological processes, but are often not properly controlled in in vitro models, introducing a significant bias in experimental outcomes. Abstract : Variations in oxygen levels play key roles in numerous physiological and pathological processes, but are often not properly controlled in in vitro models, introducing a significant bias in experimental outcomes. Recent developments in microfluidic technology have introduced a paradigm shift by providing new opportunities to better mimic physiological and pathological conditions, which is achieved by both regulating and monitoring oxygen levels at the micrometre scale in miniaturized devices. In this review, we first introduce the nature and relevance of oxygen-dependent pathways in both physiological and pathological contexts. Subsequently, we discuss strategies to control oxygen in microfluidic devices, distinguishing between engineering approaches that operate at the device level during its fabrication and chemical approaches that involve the active perfusion of fluids oxygenated at a precise level or supplemented with oxygen-producing or oxygen-scavenging materials. In addition, we discuss readout approaches for monitoring oxygen levels at the cellular and tissue levels, focusing on electrochemical and optical detection schemes for high-resolution measurements directly on-chip. An overview of different applications in which microfluidic devices have been utilized to answer biological research questions is then provided. In the final section, we provide our vision for further technological refinements of oxygen-controlling devices and discuss how these devices can be employed to generate new fundamental insights regarding key scientific problems that call for emulating oxygen levels as encountered in vivo . We conclude by making the case that ultimately emulating physiological or pathological oxygen levels should become a standard feature in all in vitro cell, tissue, and organ models.